2014
DOI: 10.1126/scitranslmed.3009512
|View full text |Cite
|
Sign up to set email alerts
|

Broadly neutralizing antibodies abrogate established hepatitis C virus infection

Abstract: Hepatitis C virus (HCV) establishes a chronic infection in the majority of exposed individuals and can cause cirrhosis and hepatocellular carcinoma. The role of antibodies directed against HCV in disease progression is poorly understood. Neutralizing antibodies (nAbs) can prevent HCV infection in vitro and in animal models. However, the effects of nAbs on an established HCV infection are unclear. Here, we demonstrate that three broadly nAbs, AR3A, AR3B and AR4A, delivered with adeno-associated viral (AAV) vect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
205
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 205 publications
(221 citation statements)
references
References 55 publications
8
205
1
1
Order By: Relevance
“…As a comparison, HSA was measured in plasma or sera from three healthy individuals (Donors 1-3). To note, HSA levels in engrafted mice are in accordance with a recently published study on humanized liver in NOD FRG mice (65). E, correlation between HSA and the repopulation index that represents the percentage of human FAH-positive cells in liver sections from PHH-engrafted FRG mice.…”
Section: Frg Mice With Highly Reconstituted Human Liver Allow Productsupporting
confidence: 63%
“…As a comparison, HSA was measured in plasma or sera from three healthy individuals (Donors 1-3). To note, HSA levels in engrafted mice are in accordance with a recently published study on humanized liver in NOD FRG mice (65). E, correlation between HSA and the repopulation index that represents the percentage of human FAH-positive cells in liver sections from PHH-engrafted FRG mice.…”
Section: Frg Mice With Highly Reconstituted Human Liver Allow Productsupporting
confidence: 63%
“…More recently, it has been proposed that the development of a profile consisting of antibodies capable of neutralizing diverse HCV strains (a broadly neutralizing antibody [bNAb]profile) predicts the clearance of acute infection in a cohort infected with genotype 1a (gt1a) HCV (12). Further studies have suggested that bNAbs may be able to control the levels of virus and contribute to clearance even after infection has become established (13). In one case in which a chronically infected patient spontaneously cleared HCV, a bNAb response was initially generated, and subsequently, T cell activity was restored and the infection was resolved (5).…”
mentioning
confidence: 99%
“…When CD81 and OCLN are overexpressed through adenoviral delivery (21) or transgenically (22), HCV can enter mouse hepatocytes in vivo. While such genetically humanized mice have proven to be useful to study HCV entry and to test approaches focusing on blocking HCV entry (21,(23)(24)(25), a shortcoming is the unphysiologically high expression level achieved by these heterologous expression approaches. Also, neither CD81 nor OCLN is uniquely expressed in the liver; rather, CD81 and OCLN are expressed on all nucleated cells and all tight junctions, respectively.…”
mentioning
confidence: 99%